PENGARUH PENERAPAN MODEL PBL TERHADAP HASIL BELAJAR SISWA KELAS X IPS MAN 2 PONTIANAK - Apriyani, Putri; Margiati, KY; Anasi, Putri Tipa (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research was aimed to analyze the effect of the implementation of problem based learning towards X IPS students’ Geography achievements of MAN 2 Pontianak. This was an experimental research in form of quasi experimental reseach. The population was 117 students and, the sample were taken from X IPS 1 and X IPS 3 learning class through random sampling technique to determine the experiment and control class. The data of this research were measured through measurement technique with objectivity as the tools of data measuring. The collected mean score and mean difference were calculated by t-test (polled varians) and effect size measuremment to determine the effectiveness of problem based learning implementation. The result of this research shown that the obtained t-value was greater than the t-table, which was 2,25, while the obtained effect size was 0,52. It can be concluded that there was a significant differences between the students’ mean score, and that Problem Based Learning model had moderate effect towards students’ achievement on hydrosphere dynamic learning material. Therefore, this researcher hoped that this research can contribute as an alternative teaching model for hydrosphere dynamic material on X class students.Keywords : Effectiveness, Problem Based Learning, Learning Achievement.